The Effectiveness of Government Internal Supervision in Preventing Maladministration in Public Institutions - Pani Arpandi (Dinasti Research, 2026)
Public services are a fundamental element in the implementation of government that is oriented towards fulfilling the basic needs of the community and the realization of the principle of good governance. However, the quality of public services in Indonesia still faces various problems, especially due to rampant maladministration, which results in public losses and reduces trust in public institutions. This study aims to analyze the effectiveness of internal government supervision and the role of the Ombudsman of the Republic of Indonesia in preventing maladministration, with an emphasis on regulatory aspects, the implementation of supervision, and institutional barriers. The research uses a descriptive qualitative method, drawing on a literature review of laws and regulations, APIP reports, and the results of the Ombudsman's examination. The results of the study show that the government's internal supervision plays a strategic role in ensuring the implementation of public services in accordance with the principles of AUPB and the service standards stipulated in Law No. 25 of 2009. However, the effectiveness of supervision remains constrained by the Ombudsman's limited authority, the lack of clarity in service standards, and the weak implementation of the government's internal control system (SPIP). These findings affirm the importance of strengthening APIP's independence, improving the Ombudsman's technical regulations, improving the competence of the apparatus, and the existence of political will from all stakeholders. Thus, efforts to prevent maladministration not only require strong regulatory tools but also consistent implementation to realize transparent, accountable, and fair public services.